Ms1 RNA Interacts With the RNA Polymerase Core in Streptomyces coelicolor and Was Identified in Majority of Actinobacteria Using a Linguistic Gene Synteny Search - Vaňková Hausnerová, Viola; Marvalová, Olga; Šiková, Michaela; Shoman, Mahmoud; Havelková, Jarmila; Kambová, Milada; Janoušková, Martina; Kumar, Dilip; Halada, Petr; Schwarz, Marek; Krásný, Libor; Hnilicová, Jarmila; et al. (Frontiers in Microbiology, 2022)
Bacteria employ small non-coding RNAs (sRNAs) to regulate gene expression. Ms1 is a sRNA that binds to the RNA polymerase (RNAP) core and affects the intracellular level of this essential enzyme. Ms1 is structurally related to 6S RNA that binds to a different form of RNAP, the holoenzyme bearing the primary sigma factor. 6S RNAs are widespread in the bacterial kingdom except for the industrially and medicinally important Actinobacteria. While Ms1 RNA was identified in Mycobacterium, it is not clear whether Ms1 RNA is present also in other Actinobacteria species. Here, using a computational search based on secondary structure similarities combined with a linguistic gene synteny approach, we identified Ms1 RNA in Streptomyces. In S. coelicolor, Ms1 RNA overlaps with the previously annotated scr3559 sRNA with an unknown function. We experimentally confirmed that Ms1 RNA/scr3559 associates with the RNAP core without the primary sigma factor HrdB in vivo. Subsequently, we applied the computational approach to other Actinobacteria and identified Ms1 RNA candidates in 824 Actinobacteria species, revealing Ms1 RNA as a widespread class of RNAP binding sRNAs, and demonstrating the ability of our multifactorial computational approach to identify weakly conserved sRNAs in evolutionarily distant genomes.